Does CSR governance matters for corporate value creation: exploring the nexus between corporate sustainability governance and investment efficiency of acquirers in Pakistan - Adeela Rustam; Geng Chengxuan (Environmental Science and Pollution Research, 2022)

Migration of organic carbon and trace elements in the system glacier-soil in the Central Caucasus alpine environment - Ivan Kushnov; Evgeny Abakumov; Rustam Tembotov; Timur Nizamutdinov (Journal of Mountain Science, 2022)

Detrital zircon U-Pb-Hf isotopes and whole-rock geochemistry of Ediacaran - Silurian clastic sediments of the Uzbek Tienshan: sources and tectonic implications - Dmitry Konopelko; Inna Safonova; Alina Perfilova; Yury Biske; Rustam Mirkamalov; Farid Divaev; Pavel Kotler; Olga Obut; Bo Wang; Min Sun; Natalia Soloshenko (International Geology Review, 2022)

Characterisation of the Mouse Cerebellar Proteome in the GFAP-IL6 Model of Chronic Neuroinflammation - Rustam Asgarov; Monokesh K. Sen; Meena Mikhael; Tim Karl; Erika Gyengesi; David A. Mahns; Chandra S. Malladi; Gerald W. Münch (The Cerebellum, 2022)

Physical and chemical properties of dust in the Pre-Aral region of Uzbekistan - Rustam Bazarbayev; Biao Zhou; Atabek Allaniyazov; Guanggen Zeng; Damir Mamedov; Evgenia Ivanitskaya; Qingzhu Wei; Hongqiang Qian; Komiljon Yakubov; Mohsen Ghali; Smagul Karazhanov (Environmental Science and Pollution Research, 2022)
The aim of this work is study of physical and chemical properties of dust of the Pre-Aral region of Uzbekistan such as Karakalpakstan and Khorezm that are located near the three deserts such as the Aralkum, Karakum, and Kyzylkum. The dust particles fell on glass have been collected in Karakalpakstan and Khorezm and studied systematically by employing wide range of methods. Particle volume vs size distribution has been measured with maximum around 600 nm and ~ 10 µm. The major and minor constituent materials present in the dust have been studied systematically by X-ray fluorescence spectroscopy, energy dispersive X-ray diffraction, and inductively coupled plasma optical emission spectroscopy. Main characteristic absorption bands corresponding to Si–O, Si–O-Si bonding in quartz and Fe–O bonds in hematite Fe 2 O 3 have been identified by infrared and Raman spectroscopy. Quartz, hematite, lime, corundum, magnesia, and several other trace minerals have been identified in the dust particles. X-ray diffraction peaks corresponding to quartz, hematite, and corundum are sharp and are found to be more crystalline with some level of disorder. Analysis of the particle size and crystallinity on human being has been performed: disordered or crystalline quartz can create the lung disease; the particles in the size of 0.5–0.7 µm may produce diseases such as chronic silicosis, silicosis, and silica tuberculosis whereas hematite might create lung disease. Dust particles worsen optical transmittance of glass of the panels. Graphical abstract